How do aggression source, employee characteristics and organisational response impact the relationship between workplace aggression and work and health outcomes in healthcare employees? A cross-sectional analysis of the National Health Service staff survey in England. Issue 8 (13th August 2020) - Cheng, Shannon; Dawson, Jeremy; Thamby, Julie; Liaw, Winston R; King, Eden B
Abstract : Objectives: To examine the prevalence of aggression in healthcare and its association with employees' turnover intentions, health and engagement, as well as how these effects differ based on aggression source (patients vs colleagues), employee characteristics (race, gender and occupation) and organisational response to the aggression. Design: Multilevel moderated regression analysis of 2010 National Health Service (NHS) survey. Setting: 147 acute NHS trusts in England. Participants: 36 850 participants across three occupational groups (14% medical/dental, 61% nursing/midwifery, 25% allied health professionals or scientific and technical staff). Main outcome measures: Employee turnover intentions, health and work engagement. Results: Both forms of aggression (from patients and colleagues) have significant and substantial effects on turnover intentions, health and work engagement; however, for all three outcome variables, the effect of aggression from colleagues is more than twice the size of the effect of aggression from patients. Organisational response was found to buffer the negative effects of aggression from patients for turnover intentions and the negative effects of aggression from patients and colleagues for employee health. The results also demonstrated that nurses/midwives, women and Black employees are more likely to experience aggression; however, no clear patterns emerged on how aggression differentially impacts employees of different races, genders and occupations with respect to the outcome variables. Conclusions: Although aggression from patients and colleagues both have negative effects on healthcare employees' turnover intentions, health and work engagement, these negative effects are worse when it is aggression from colleagues. Having an effective organisational response can help ameliorate the negative effects of aggression on employees' health; however, it may not always buffer negative effects on turnover intentions and work engagement. Future research should examine other approaches, as well as how organisational responses and resources may need to differ based on aggression source.